Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.47070/ijapr.v9i4.1837
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Review of Pharmcological Activities of Notchi Kudineer- A Siddha Herbal Decoction Used in Covid-19

Abstract: COVID-19 Caused by the novel corona virus (SARS-CoV-2), which has already pushed the entire global community to change their priorities towards finding a suitable anti-viral medicine and a vaccine. While most of the countries have started to prescribe vaccines, which show varied levels of efficacy, finding an effective anti-viral medicine against the virus is still in the early stages despite full-fledged research activities at global level. Many countries particularly those having a rich traditional health sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Siddha medicines probably have a similar anti-inflammatory action to the repurposed conventional drugs used in the pandemic and comparatively cost-effective treatment which needs to be explored in the future. Previously published works indicate that the ingredients of Kaba sura kudineer, Adhathodai manapaagu, Amukkara Chooranam Mathirai, Bramanandha Bairavam Mathirai, and Notchi kudineer are having Anti-viral, Anti-inflammatory, Anti-asthmatic, anti-diarrheal, and analgesic activities ( 13 ) ( 38 ). The molecular target action of the anti-inflammatory action of Kaba Sura Kudineer revealed the suppression of LPS induced pro-inflammatory cytokines TNF-α, IL-6, and PGE2 levels that owe to the present treatment outcomes of the study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Siddha medicines probably have a similar anti-inflammatory action to the repurposed conventional drugs used in the pandemic and comparatively cost-effective treatment which needs to be explored in the future. Previously published works indicate that the ingredients of Kaba sura kudineer, Adhathodai manapaagu, Amukkara Chooranam Mathirai, Bramanandha Bairavam Mathirai, and Notchi kudineer are having Anti-viral, Anti-inflammatory, Anti-asthmatic, anti-diarrheal, and analgesic activities ( 13 ) ( 38 ). The molecular target action of the anti-inflammatory action of Kaba Sura Kudineer revealed the suppression of LPS induced pro-inflammatory cytokines TNF-α, IL-6, and PGE2 levels that owe to the present treatment outcomes of the study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 10 ) The individual herbal formulations of Aadathodai Manapagu (AM)( 11 ) , Notchi Kudineer (NK) inhibit the SARS-CoV-2 virus in in-vitro studies. In-silico studies have indicated that phytoconstituents in Kaba Sura Kudineer (KSK)( 12 ), Notchi Kudineer (NK)( 13 ), Adathodai Kudineer (AK)( 14 ) , Thontha Sura Kudineer (TSK)( 12 ), target the spike protein of SARS-CoV-2 virus, thereby making them potential drugs. KSK, a Siddha medicine with 15 herbs, showed a high binding affinity against SARS-CoV-2 spike protein.…”
Section: Introductionmentioning
confidence: 99%